Coach-athlete relationship and associated background factors: an analysis in brazilian coaches (Research, Society and Development, 2020)
This study aimed to analyze the antecedent factors associated with the coach athlete relatioship (CART) from the perspective of Brazilian coaches. 182 Brazilian coaches of both sexes, with an average age of 40.47 ± 9.7 years, participating in the 2015 Youth School Games were subjected. As instruments were used: identification form, Coach-Athlete Relationship Questionnaire (CART-Q coach version) and the Basic Needs in Sports Satisfaction Scale (BNSSS). Data were analyzed using descriptive and inferential statistics using Binary Logistic Regression (p